2009
DOI: 10.1007/s12011-008-8305-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 35 Inorganic Elements in Teeth in Relation to Caries Formation

Abstract: As caries is a most common affliction of teeth, which are predominantly composed of inorganic elements, it was considered worthwhile to determine their elemental composition and to find if it bears any relation to caries formation. For this purpose, 35 inorganic elements were determined in 15 non-carious and an equal number of carious whole teeth after their dissolution in nitric acid. The results showed that out of 35 elements, strontium was the only element found to be present in significantly lower amount i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Strontium was supposed to have a cariostatic effect if administered prenatal compared to post-natal, as demonstrated in rodents [9]. In carious teeth the concentration of strontium was significantly lower when compared to intact teeth [10][11]. Blood concentration of strontium, phosphate and fluorine was significantly lower in patients with high carious activity in comparison with patients with low carious activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Strontium was supposed to have a cariostatic effect if administered prenatal compared to post-natal, as demonstrated in rodents [9]. In carious teeth the concentration of strontium was significantly lower when compared to intact teeth [10][11]. Blood concentration of strontium, phosphate and fluorine was significantly lower in patients with high carious activity in comparison with patients with low carious activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows significantly high boron in blood of carious persons. This element was also high in carious teeth in our recent study [4]. Boron occurs in very large concentrations in ocean, rocks, and soil and is also present in plants and water [7].…”
Section: Resultsmentioning
confidence: 77%
“…This is supported by our recently published study in which we had found that, out of 35 elements analyzed, strontium was the only element found to be present in significantly lower amount in carious teeth. The mean strontium content of carious teeth was 238 ppm as opposed to 389 ppm in non-carious sound teeth [4]. The experimental proof of beneficial effect of strontium in preventing calcium loss from teeth is provided by our recent study in which we had found that strontium pre-treatment of both carious as well as sound teeth resulted in a significant decrease in calcium released from them when immersed in 1% lactic acid [15].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…A series of papers contained arguments for relation between heavy metal content and the number of carries of patients, but according to literature data [1,4,5] it is difficult to have a clear conclusion in this moment [7][8][9]. First of all the number of carries as an expression of oral health could be the result of many other social factors, and despite the fact that the environment quality is a part of quality of life, it is very difficult to be sure that the teeth are collected from a target group with similar life conditions.…”
Section: Introductionmentioning
confidence: 99%